Screening for light personalities in Portugal: a cross-cultural validation of the light triad scale with an at-risk-of-delinquency sample - Pechorro, Pedro (2024)
The Light Triad of personality refers to three prosocial personality traits-Faith in Humanity, Humanism, and Kantianism-that promote the worth and dignity of other people, focus on ethical behavior and empathy, and confidence that other people are naturally good. The aim of the present study is to examine the psychometric properties of the Light Triad Scale (LTS)-Portuguese version. Our convenience sample consisted of 242 male and female participants (M = 30.19 years, SD = 12.78, range = 16-77) from Portugal. The proposed latent structure models of the LTS obtained adequate fits. Internal consistency/reliability, as measured by the alpha and omega coefficients, was adequate to good. Construct validity with other psychometric measures (i.e., empathy, dark traits of personality, propensity to morally disengage, and antisociality/criminality measures) and criterion-related validity (with justice involvement variables such as problems with the law, arrested by the police, sentenced to prison and alcohol/drug abuse variables) were demonstrated. Cross-gender measurement invariance was established, with females scoring higher than males. The findings support the use of the LTS as a valid and reliable measure.